Improving Students Learning Outcomes through Peer Tutoring with Cooperative Settings - Kaharuddin, Andi (Journal of Mathematical Pedagogy (JoMP), 2019)
This study found the low of student learning outcomes. This study aims to improve student learning outcomes through peer tutoring method of cooperative settings. The type of research is classroom action research (CAR) that consisting of: (1) planning, (2) implementing, (3) observing and (4) reflecting. This action research consisted of 2 cycles and each cycle consisted of 3 meetings. The subjects of this study are VIII.D Junior High School of Puriala 1l, with the total consists of 28 students, 15 male and 13 female. Technique of collecting data used observation and tests. The data obtained that is analyzed descriptively.  The results of data analysis showed that in cycle I,, students who get more than and equal to 65 is 17 students with the percentage 60.71 %. In cycle 2, the score has increased. There are 22 students who gained more than and equal to 65 as presentations reached 78.57%Keywords: Cooperative, Learning Outcomes, Peer Tutors.